The Double Edge Sword of “High Potential” Expectations - Igor Kotlyar (Europe's Journal of Psychology, 2013)
Many organizations categorize employees in terms of potential, labeling some as “high potential” employees. This practice of labeling employees based on their performance potential can create differentiated expectations of performance and, thus, impact their attitudes and behaviors. However, research has not examined the impact of such labels on the recipients’ attitudes following performance feedback. In our laboratory study of 477 undergraduate business students from a large North American university, we examined the effect of “high potential” expectations on task commitment and satisfaction following positive and negative feedback. Our results indicate that such labels can make individuals more sensitive to feedback and consequently create unintentional negative effects on commitment and satisfaction.